2020
DOI: 10.3390/antiox9050400
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Nutraceutical Potential of Dried Pepper Capsicum annuum L. on Market from Altino in Abruzzo Region

Abstract: Sweet pepper is a typical type of Capsicum annuum from Abruzzo region, recognized as a traditional and local product, traditionally cultivated in the town of Altino (Abruzzo region, Italy). The aim of this study is to compare the sweet type of peppers from Altino with the hot pepper cultivated in the same area, in order to delineate their different phytochemical and biological profiles in vitro and in vivo. In this study, we elucidated their phytochemical composition, fatty acids composition and phenolic/flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 39 publications
1
21
0
2
Order By: Relevance
“…The MTT (3‐(4, 5‐dimethyl thiazole‐2‐yl)‐2, 5‐diphenyltetrazolium bromide) colorimetric assay has over the years shown to be an effective and affordable method in determining the cytotoxic effect of drugs and plant phytochemical constituents on normal and cancer cells. This is evident in several studies reporting the cytotoxicity of phenolics and other phytochemicals on different cell lines (Della Valle et al., 2020; Mollica et al., 2018).…”
Section: Introductionmentioning
confidence: 86%
“…The MTT (3‐(4, 5‐dimethyl thiazole‐2‐yl)‐2, 5‐diphenyltetrazolium bromide) colorimetric assay has over the years shown to be an effective and affordable method in determining the cytotoxic effect of drugs and plant phytochemical constituents on normal and cancer cells. This is evident in several studies reporting the cytotoxicity of phenolics and other phytochemicals on different cell lines (Della Valle et al., 2020; Mollica et al., 2018).…”
Section: Introductionmentioning
confidence: 86%
“…For the preparation of grape pomace extracts and seeds oil, 500 mg of freeze-dried material or crushed seeds were used following the procedure reported by Della Valle et al [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it still is of utmost interest to assess the specific phenolic composition of different sweet pepper cultivars, as well as to establish the possible effects of the production system and maturation stage. Indeed, it has been previously reported that the phenolic profiles alone or coupled with other chemical data (e.g., volatile fraction composition and antioxidant activity data, among others) allowed for differentiating peppers' cultivars [26,28], such as red pepper cultivars grown under different shade and controlled-temperature conditions [20], fresh and cooked sweet peppers of two cultivars [27], sweet and hot peppers [29] as well as fresh and dried red peppers grown under conventional or organic systems [16]. Recently, the research team has shown that chemical-sensory data and potentiometric signal profiles, recorded using a lab-made electronic tongue could be satisfactorily used as biomarkers of sweet peppers' agronomic production system (organic versus conventional) and the maturation stage (green versus red fruits) [30].…”
Section: Introductionmentioning
confidence: 99%